THE REPRODUCTIVE FUNCTION OF WOMEN AFTER DESTRUCTIVE OPERATIONS ON THE CERVIX - F. F. Badretdinova; V. V. Kortunova (Акушерство, гинекология и репродукция)
Retrospectively reviewed results of treatment of 147 women with benign diseases of the cervix, which was destructive treatment of pathologic cervical lesion. Examination of patients included: bakterioskopiâ smear, cytology smears, PCR diagnosis of sexually transmitted infections, advanced colposcopy with biopsy sighting testimony to the destructive treatment were the result of scar deformity ectropion of cervix (91-61.9%), pathology of the CMM combined with human papillomavirus infection (25-17.0%), dysplasia (9-6.1%), Leukoplakia (12-8.2%), cervical polyp (6-4.0%), endometriosis, CMM (4-2.7%). Group of comparison comprised 81 women with the same pathology but without the destructive interventions on the neck. After a destructive treatment in terms from 1 till 5 years pregnancy occurred at 56 (38.1%) women. Spontaneous miscarriages have been observed in 27 (28.4%) women. Nearly one-third of pregnancies in women major group (29 women) has ended medical abortion After conization of cervix regardless of how the pregnancy was significantly more complicated by her amnion protrudes like a threat of termination, at different gestational ages. destructive interference in the cervix a little (statistically unreliable p≥0.05) affect the course of pregnancy, however, there is a dependency on the reproductive function of the type and depth of destructive interference.